Driving Sustainability: The Impact of Green Business Practices on Organizational and Economic Performance in Nepal - Saud, Rajendra Singh; Devkota, Niranjan; Paudel, Udaya Raj; Lawaju, Purnima (International Research Journal of MMC, 2026)
The global business landscape is undergoing a critical transition towards a Green Economy (GE), emphasizing sustainable practices to balance environmental, social, and economic objectives. However, little is known about the specific drivers and outcomes of green business adoption within developing economies like Nepal. In this study, we examine the influence of key organizational factors on the adoption of Green Business Practices (GBP) and their subsequent impact on multidimensional performance, identifying implementation obstacles and providing managerial solutions for promoting a GE in Nepal, using a framework integrating the Resource-Based View (RBV), Natural Resource-Based View (NRBV), and Institutional Theory, analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). We tested a total of 10 hypotheses. Primary data were collected from 405 respondents across business organizations, primarily within the Kathmandu Valley, Nepal. The study reveals that Green Human Capital (GHC) [(β = 0.159, p<0.01)], Green Logistic Management (GLM) [(β = 0.277, p<0.01)], and Green Organizational Commitment (GOC) [(β = 0.446, p<0.01)] significantly impact the adoption of Green Business Practices (GBP). In turn, GBP has a strong, significant positive influence on Environmental Performance (β = 0.719, p<0.01), Economic Performance (β = 0.639, p<0.01), Organizational Performance (β = 0.665, p<0.01), and Social Performance (β = 0.623, p<0.01). Key obstacles identified include a lack of knowledge, inability to adapt to new trends, and insufficient governmental supervision and policy implementation. Managerial solutions emphasize the need for awareness campaigns, skill development, supportive policies, and committed leadership. This study provides valuable insights for policymakers, business leaders, and development practitioners, enabling them to understand the critical levers for fostering a Green Economy through corporate sustainability in Nepal.